The Role of Fine-Wire Localization Breast Biopsy in the Management of BI-RADS Category 4-5 for Non-Palpable Breast Lesions: An Experience at King Abdulaziz University Hospital, Saudi Arabia - Zuhoor K. Al Gaithy, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study is to determine a positive predictive value for malignancy in patients initially categorized as having Breast Imaging Reporting and Data System categories 4 and 5 with non-palpable breast lesions that underwent fine wire-localized biopsy. 116 patients underwent this process at the Surgery Department, King Abdulaziz University Hospital, Saudi Arabia: from December 2007 through November 2009. By histopathology, out of 116 patients, 76 (65.52%) were benign and 44 (37.93%) malignant lesions. According to Breast Imaging Reporting and Data System categories: 89 (76.72%) were category 4 and 27 (23.28%) were category 5. In category 4, 70.80% (n=64) of cases were benign and 28.10% (n=25) were malignant given positive predictive value 28.09%. In category 5, 29.60% (n=8) of cases were benign and 70.10% (n=19) were malignant given positive predictive value 70.73% after fine wire-localized biopsy for non-palpable breast lesions. In conclusion, combination of Breast Imaging Reporting and Data System categories and fine wire-localized biopsy for non-palpable breast lesions is safe, but the positive predictable value of malignancy of Breast Imaging Reporting and Data System was low especially in category 4. Preoperative histological confirmation is very important for suspicious non-palpable breast lesions to avoid unnecessary open breast biopsy.